Lawsone: A novel reagent for the detection of latent fingermarks on paper surfaces - Jelly, R.; Lewis, Simon; Lennard, C.; Lim, K.; Almog, J. (The Royal Society of Chemistry, 2008)
Lawsone (2-hydroxy-1,4-naphthoquinone) 5 reacts with latent fingermark deposits on paper surfaces to yield purple-brown impressions of ridge details which are also photoluminescent; this compound represents the first in a completely new class of fingermark detection reagents.